Memoirs of Costa Rica. Imaginary postcards (Tzintzun, Revista de Estudios Históricos, 2016)
It is necessary to find explanations in the images from the past to understand theways in which the world was represented, and how their creators -or their read-ers- used to see these images. This paper’s objective is to make an approach toCosta Rica postcards edited from 1900 to 1920, trying to show that they can offer alot of benefits to the knowledge of history, specifically when in the images we canrecognize visual discourses later adopted as social imaginaries. There are somepublications with the mission of recollecting, postcards, and those are significant,but it is more important to go even further and develop an iconological reading,that can give us examples of the richness of the visual messages.
Keywords: Costa Rica; postcards; reading images; visual discourse; Iconology; Banana in Central America; Latin America post cards